Improving poultry production in the tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Poultry, by Anthony J Smith Tropical Agriculturalist series Macmillan and CTA, 218pp 1990, ISBN 0 333 52306 7 Available from Macmillan Publishers Ltd 4 Little Essex Street, London WC2, UK and from CTA for nationals of ACP countries